ANALISIS KRIMINOLOGIS FREKUENSI KEJAHATAN PENCURIAN DENGAN KEKERASAN DI WILAYAH HUKUM RESORT MAMUJU UTARA - Saddam, Saddam (Katalogis, 2015)
The research problem was â€œHow is the stealing frequency with violence at legalÂ area of North Mamuju Resort and how is the prevention efforts and overcoming of stealing with violence at legalÂ of area North Mamuju Resort?. This research employed Juridical Sociology approach to review the relationship of legal and illegal aspect with qualitative method that would expose something concerning social reality and attitude of law maintain. The research result indicates that the frequency of stealing with violence occurred at North Mamuju Resort of the last five years is from 2010 to 2014 where in 2012 increased enough with the cause of unstable of society economy. In addition, there is additional of job seekers as the interview result and what police department based on criminal statistics and overcoming effort of stealing with violence at North Mamuju Resort is doing preventive action as how they protect the society and make them wealth and maintain the law.